PENDAMPINGAN DIGITALISASI UKM: PELATIHAN MEDIA SOSIAL PADA VIGAZA FARM SEBAGAI UPAYA PENINGKATAN DAYA SAING - Andriani, Ria; Pujianto, Ade (Universitas Mataram, 2024)
Vigaza Farm is a small and medium-sized enterprise (SME) operating in the livestock sector and was established in 2010, providing a variety of poultry and fish for consumption. Currently, the main focus of this business is on quails. Amid global and local challenges, livestock SMEs often face obstacles in accessing markets and building closer relationships with consumers, resulting in difficulties in promoting themselves and expanding their reach. This Community Service Program aims to provide assistance in the digitalization of SMEs, with an emphasis on training for the creation and management of social media platforms, particularly Instagram, for Vigaza Farm. The methods used in this activity include training, mentoring, and evaluating the use of Vigaza Farm's social media. This training successfully enhanced the branding of Vigaza Farm and improved the technical skills of its managers in utilizing technology to create engaging content. As a result, the number of followers on Instagram significantly increased from 23 to 500 followers, and sales rose from 50 bundles per week to 150 bundles shipped to various cities in Indonesia, including Jakarta. Currently, Vigaza Farm also serves as a supplier of quail eggs and quails for activities organized by the Millennial Farmers Group of Sleman. This community service program has successfully improved Vigaza Farm's digital capabilities, expanded market reach, and significantly increased sales.